Science at Cross Fire: a rethorical análisis of criticism in a Spanish medical discourse - Ariza, María Ángeles Alcaraz; Salager-Meyer, Françoise (The ESPecialist, 2012)
This research analyzes the quantitative and qualitative evolution of critical comments in 76 medical papers written in Spanish and published between 1930 and 1999 and relates the variations observed to the historico-social context that surrounded the production of these papers. Our results show that criticism in Spanish-written medical prose has always been very harshly and directly formulated at least up to the 1990’s ‘cutting off’ period which marked not only an increase in the frequency of critical comments, but also a rhetorical switch toward linguistic mitigation. We conclude that the evolution of the rhetorical features of criticism in Spanish medical prose resembles that of French medical discourse, but that the Anglo-American hedged way of dissenting with one’s peers is progressively influencing the expression of today’s Spanish academic criticism.